EXTRAPULMONARY TUBERCULOSIS PATIENT'S PROFILE IN RSUD CIANJUR 2017 – 2019 - Hariyani, Rizqi Primasane; Ferdiana, Fita; Hadipoetro, Ferial (Faculty of Medicine and Health Universitas Muhammadiyah Jakarta, 2020)
Background: Tuberculosis is one of the 10 causes of death in the world1. Indonesia represents the third country for tuberculosis incidence. Based on the WHO data, the number of extra-pulmonary tuberculosis (EPT) in 2017 is around 896,000 cases, that was 14% of 6.4 million tuberculosis patients2. The incidence of EPT in Indonesia, in 2012, was 17,420 cases from total of 331,424 cases3. So far there was no profile data about EPT in RSUD Cianjur even number of EPT who has been diagnosed by histopathological examination was done. Objective of this study was to determine EPT patient’s profile in RSUD Cianjur 2017 – 2018. Methods: Design of study was cross sectional, 183 samples obtained from the anatomic pathology laboratory data and the medical record for the period January 2017 - May 2019. Results: The results of the study show that the number of EPT patients at RSUD Cianjur in 2017, 2018 and 2019 is as many as 60, 71, and 52 patients. There were 10 patients 15 years of age, 148 patients between 15-50 years of age, and 25 patients 50 years of age. There were 84 male patients and 99 female patients. According to the location, 63 cases occurred in lymph nodes, 67 in the digestive system, 20 in the musculoskeletal system, 25 in the reproductive system, 6 in the thorax, 1 in the thyroid and 1 in the bone marrow. Conclusion: The proportion of patients with EPT in RSUD Cianjur in 2017 – 2019 was 6% of all tuberculosis patients. The percentage of the patients 15 years of age was 5.5%, between 15-50 years of age was 80.87%, and 50 years of age was 13.66%. Of these patients 46% were male and 54% were female. The infected location in the digestive system was 36.61%, lymph nodes were 34.43%, reproductive system was 13.66%, musculoskeletal system was 10.93%, thorax was 3.28%, thyroid was 0.55% and bone marrow was 0.55%.